Outcrossing and heterozygosity rates in tropical onion populations - Fernandes Santos, Carlos Antonio; Souza Alves , Ítala Layanne de (Comunicata Scientiae, 2022)
Outcrossing and heterogosity rates are important for defining genetic conservation and breeding strategies, and these estimates are quite rare to onion. The aim of this study was to estimate cross-pollination and heterozygosity rates in tropical onion populations to guide development of new varieties. Eight tropical onion pairs were field isolated to be open pollination by insects. Parents vernalized bulbs were used for pair crossing, in alternate rows, 1:1. Seeds were harvested from the female parent to assess the progenies outcrossing and heterogigosity rates based on color of the red bulb, partially dominant over yellow, and four microsatellite loci. The outcrossing rates estimated with morphological marker, in the ‘BRS Rio Vale’ × ‘BRS Carrancas’, ‘Botucatu’ × ‘BRS Carrancas’, ‘IPA 11’ × ‘IPA 10’ and ‘BRS Alfa São Francisco’ × ‘IPA10’ crosses, ranged from 15% to 39%, with an average of 28.2%, while with microsatellite loci, in the ‘BRS Alfa São Francisco’×’IPA 11’, ‘Alfa SF RT’ × ‘BRS A. São Francisco’, ‘BRS Rio Vale’ × ‘Botucatu’ and ‘Cascuda T6’ × ‘Botucatu’ crosses, ranged from 33% to 71%, with an average of 42.7%, indicating a mixture of cross-pollination and self-pollination within progenies. The average values ​​of heterozygosity in the eight populations ranged from 0.82 to 1.0, indicating the possibility of developing open pollinated onion varieties with greater adaptation to biotic and abiotic stresses.